Incidence and Risk Factors of Peripheral Artery Disease Recurrence in Patients Who Underwent Angioplasty or Stenting - Muhammad Irfan Shahzad Anjum, Muhammad Umair, Awais Ghulam Nabi, Aasim Ali Sajid, M. Mustansar Mansoor Gill (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study was conducted to assess the incidence and risk factors of peripheral artery disease recurrence in patients who underwent angioplasty or stent. Methodology: A retrospective study was conducted in the Department of Cardiology of Faisalabad Institute of Cardiology from January 2021 to January 2023. A total of 100 patients presenting at the hospital with lower extremity peripheral artery disease diagnosed by ankle-brachial index or ultrasound were included in the study by consecutive sampling. Inguinal region was percutaneously accessed via iliac artery and a balloon expandable stent was deployed followed by additional stenting with dynamic balloon stent. A drop of more than 0.1 in the ankle-brachial index and >50% degree of stenosis at follow up indicated recurrence which was evaluated by angiography. Results: Out of 100, twelve patients (12%) showed restenosis on follow-up and 88 (88%) had a successful procedure, free of recurrence. The rate of recurrence insignificantly related to gender (OR = 9.0, 95% CI 1.42–57.1, p=0.68), smoking (OR = 9.0, 95% CI 1.42–57.1, p=0.09), diabetes (OR = 15.0, 95% CI 2.03–111.1, p = 0.09), hypertension (OR = 9.0, 95% CI 1.42–57.1, p=0.22) and dyslipidemia (p=0.47). The significant predictors of PAD recurrence were external iliac and common iliac involvement (p=0.05) and use of balloon retransmitted stent (p=0.008). Conclusion: It is concluded that the incidence of peripheral artery disease recurrence was low in patients undergoing angioplasty or stenting. It was significantly associated with type of vessel involved and endovascular revascularization technique. Keywords: Peripheral Artery Disease Recurrence, Angioplasty or Stenting, Department of Cardiology